Differentiation between some Ulva spp. by morphological, genetic and biochemical analyses - M. M. Ismail; E. S. Mohamed (Вавиловский журнал генетики и селекции)
Ulva is most common green seaweed in Egypt coast, it used as a source of food, feed, medicines and fertilizers in all the world. This study is the first time to investigate the morphological, genetic and biochemical variation within four Ulva species collected from Eastern Harbor, Alexandria. The morphology description of thallus showed highly variations according to species, but there is not enough data to make differentiation between species in the same genus since it is impacted with environmental factors and development stage of seaweeds. Genetic variations between the tested Ulva spp. were analyzed using random amplified polymorphic DNA (RAPD) analyses which shows that it would be possible to establish a unique fingerprint for individual seaweeds based on the combined results generated from a small collection of primers. The dendrogram showed that the most closely species are U. lactuca and U. compressa, while, U. fasciata was far from both U. lactuca and U. compressa. Meanwhile, U. linzea is showed to be a unique species. The biochemical composition (e.g. protein, carbohydrate, lipid and pigment composition) of the collected Ulva spp. grouped the collected Ulva spp. into two groups (U. fasciata and U. lactuca) and other (U. compressa and U. linzea).